An elevated creatine kinase in the context of influenza A infection and sickle cell trait. Issue 1 (26th June 2019) - Bamber, H.; Rudge, B.; Vercueil, A.
Summary: We describe the case of a 37‐year‐old normally fit and well man who presented to hospital with fever, lethargy and myalgia. He was found to have a creatine kinase level of over 1 million IU.l −1 . He initially underwent fluid resuscitation, but despite this his renal function declined and he required continuous veno‐venous haemodiafiltration. Subsequent testing revealed a positive viral swab for influenza A and that he was a carrier of sickle cell trait. We review the literature for previous reports describing this association and demonstrate the rarity of such a presentation.